Crisis? What crisis? : Britain in the 1970s / Alwyn W. Turner. - Turner, Alwyn W. (Aurum, 2013)
'Crisis? What Crisis?' tells the story of Britain in the 1970s through the soaps and sitcoms, the music and movies, the fiction, fashion and sport of the time. It was a culture that reflected a turbulent political reality.